1994
DOI: 10.1021/jm00032a016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Activity of a New Potent Class of Anti-HIV Agents, the Peroxoniobium-Substituted Heteropolytungstates

Abstract: The mono- and trisubstituted peroxyniobium polyoxotungstates of formulas [(CH3)3NH]7[Si-(NbO2)3W9O37], Cs7[Si(NbO2)3W9O37], alpha-K5[Si(NbO2)W11O39] and alpha-[(CH3)3NH]5[Si(NbO2)-W11O39], have been prepared, purified, and characterized spectroscopically by 29Si NMR, 183W NMR, and IR. The presence of peroxo groups was verified by the yellow color of the product and quantified by iodometric titration. The potency of both the complexes and the precursor complexes was evaluated in human peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 6 publications
1
33
0
3
Order By: Relevance
“…Various POMs have been reported to interact with viral surface proteins and to inhibit the replication of several types of viruses [10][11][12][13][14]. Recent studies have shown that POMs have superior ability to selectively precipitate prion proteins, a property which could be useful in the development of immonoassays capable of detecting extremely low concentrations of infectious prions in blood and cerebrospinal fluid [15].…”
Section: Introductionmentioning
confidence: 99%
“…Various POMs have been reported to interact with viral surface proteins and to inhibit the replication of several types of viruses [10][11][12][13][14]. Recent studies have shown that POMs have superior ability to selectively precipitate prion proteins, a property which could be useful in the development of immonoassays capable of detecting extremely low concentrations of infectious prions in blood and cerebrospinal fluid [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that certain paM are significantly inhibitory to human immunodeficiency virus (HIV) in vitro (Hill et al, 1990(Hill et al, , 1993Yamamoto et al, 1992;Inouye et al, 1993;Blasecki, 1994;Judd et al, 1994;Kim et al, 1994;Swart & Meijer, 1994;Moore etal., 1995;Shigeta et al, 1995). Herpesviruses have been reported to be inhibited by some of these compounds both in vitro (Fukuma et al, 1991;Yamamoto et al, 1992;Ikeda et al, 1993) and in vivo (Ikeda et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…W 601g 2-); (6) decatungstate (W1Q0324-), and (7) the Preyssler ion [(NaP 5W3 00114)14-j (Hill etal.199Ga,b) (Table 1). The potent and selective anti-human immunodeficiency virus type-1 (HIV-1) activity of polyoxometalates in infected human peripheral blood mononuclear (PBM) cells or cultured CD4+T-cell lines was reported by several workers (Hill et el., 199Ga,b;Yamamoto et al, 1992;Kim et al, 1994). Polyoxometalates also proved broadly inhibitory against retro-, myxo-, herpes-, toga-, rhabdoand arenavirus replication in vitro (Yamamoto et al, 1992;Ikeda et al, 1993).…”
Section: Introductionmentioning
confidence: 99%